Glycine Protects Muscle Cells From Wasting in vitro via mTORC1 Signaling - Caldow, Marissa K.; Ham, Daniel J.; Trieu, Jennifer; Chung, Jin Dylan; Lynch, Gordon S.; Koopman, René (Frontiers in Nutrition, 2019)
Glycine supplementation can protect skeletal muscles of mice from cancer-induced wasting, but the mechanisms underlying this protection are not well understood. The aim of this study was to determine whether exogenous glycine directly protects skeletal muscle cells from wasting. C2C12 muscle cells were exposed to non-inflammatory catabolic stimuli via two models: serum withdrawal (SF) for 48 hours; or incubation in HEPES buffered saline (HBS) for up to 5 hours. Cells were supplemented with glycine or equimolar concentrations of L-alanine. SF- and HBS-treated myotubes (with or without L-alanine) were ~20% and ~30% smaller than control myotubes. Glycine-treated myotubes were up to 20% larger (P<0.01) compared to cells treated with L-alanine in both models of muscle cell atrophy. The mTORC1 inhibitor rapamycin prevented the glycine-stimulated protection of myotube diameter, and glycine-stimulated S6 phosphorylation, suggesting that mTORC1 signaling may be necessary for glycine’s protective effects in vitro. Increasing glycine availability may be beneficial for muscle wasting conditions associated with inadequate nutrient intake.